Cerebral Microemboli Increase β-amyloid Protein Deposition, MMP-9, and GFAP Expression in the Alzheimer’s Model of APP/PS1 Double Transgenic Mice - Ning, Min; Wu, Yiying; Ni, Xiushi; Zhao, Yanling; Ling, Rujing (Current Neurovascular Research, 2014)
We investigated the effects of cerebral arterial microemboli on amyloid β protein (Aβ) deposition in the hippocampal region of amyloid precursor protein/presenilin 1 (APP/PS1) double transgenic mice and evaluated the role of cerebral arterial microemboli in Alzheimer's disease (AD) pathogenesis. The mice were divided into a wild-type sham surgery group (n = 15), a wild-type coupled with microemboli group (n =15), an APP/PS1 double transgenic sham surgery group (n =15) and an APP/PS1 double transgenic coupled with microemboli group (n =15). The microemboli mice were injected via the left internal carotid artery with 300 µL of a normal saline suspension containing 100 whole blood clot-derived microemboli (25-50 µm). The sham surgery mice were injected with equal volumes of saline. After the mouse model was established for 1, 2 or 4 weeks, the Aβ1-42 deposition in the left hippocampal region and the matrix metalloproteinase-9 (MMP-9) and glial fibrillary acidic protein (GFAP) expression levels were determined through immunohistochemical staining. The Aβ1-42 deposition level in the left hippocampi of transgenic microemboli group was significantly greater than in the transgenic sham group at week 1 and 2 (P<0.001) but not at week 4. No Aβ1-42 deposition was detected in the wild-type groups. Only sporadic MMP-9- and GFAP-positive cells were observed in the wild-type sham group. Significantly more MMP-9- and GFAP-positive cells were detected in the transgenic groups (P<0.001), particularly in the transgenic microemboli group. An intragroup analysis of the time factor for the microemboli groups showed significantly more MMP-9- and GFAP-positive cells at week 1 than at week 2 or 4 (P<0.001). No difference was detected between time points in the sham groups. Cerebral microemboli increased Aβ deposition in the hippocampal region of APP/PS1 double transgenic mice. MMP-9 and GFAP expression may play an important role in excess Aβ deposition, which is caused by an imbalance between the protein’s synthesis and removal.
Keywords: matrix metalloproteinase-9